Pengaruh Profitabilitas, Leverage, Corporate Governance, dan Ukuran Perusahaan Terhadap Tax Avoidance (Studi Kasus Pada Perusahaan Yang Tercatat Di Jakarta Islamic Index Tahun 2012-2016) - Sunarsih Sunarsih; Slamet Haryono; Fahmi Yahya (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2019)
Taxes are a major contribution on state revenues which will then be used for national financing and development. However, taxpayers’ compliance level is still low. There are deviations made by the taxpayer in reducing taxes, in order not to get a high tax. One of them by tax avoidance. Tax avoidance is the process of controlling actions to avoid the consequences of improper taxation and is legal. The purpose of this research is to explain the effect of profitability, leverage, corporate governance, and firm size to tax avoidance. The researcher take a case study on a company listed on the Jakarta Islamic Index (JII) in 2012 until 2016. The sample are 65 samples consisting of 13 companies. Regression used in this research is panel data regression, where selected Fixed Effect as the right regression model. In this regression, the result shows that profitability as measured by ROA and firm size as measured by total asset have significant negative effect to tax avoidance, and leverage as measured by DER has a significant positive effect on tax avoidance. While corporate governance as measured by independent commissioners and audit committee does not affect tax avoidance